Amino acid composition and nutritional value of sesame seed proteins in some local and imported sesame cultivars in VietNam - Ty, Nguyen Thi; Mai, Tong Quynh; Nhi, Nguyen Bich; Chi, Phan Van (Academia Journal of Biology, 2015)
Amino acid composition of 6 local and imported sesame seed cultivars (Sesamum indicum L.) grown in Vietnam (white japanese sesame, white Bacgiang sesame, yellow Binhdinh sesame, yellow Thanhhoa sesame, black japanese sesame and black Binhdinh sesame) were analyzed by derivatization with o-phthaladehyde (OPA) for primary amino acids and 9-fluorenyl methyl chloroformate (FMOC) for secondary amino acids on HP - Amino Quant Series II (Hewlett Packard). The results showed that the total amino acid contents in the seeds of these cultivars were approximately about 17-21.5%. The total amino acid contents of the japanese sesame cultivars were higher than those of the local vietnamese ones. Among the local studied vietnamese sesame cultivars the total amino acid contents of the yellow Binhdinh one were the highest and approximately similar to the japanese ones. The sesame seed proteins were characterized by high nutritional value with the high ratios of essential amino acids in comparison with the FAO standard protein. The sesame seed proteins were rich in essential amino acids, especially lysine. No significant differences were found between 3 analyzed seasame types: white, yellow and black sesames.